Firm Liability When Third Parties and Consumers Incur Cumulative Harm - Elisabeth Schulte; Tim Friehe; Eric Langlais (ZBW - Leibniz Information Centre for Economics, 2021)
This paper analyzes liability rules when consumers and third parties/the environment incur harm. Expected harm is convex in the level of output and modeled as a power function. We show that the social ranking of liability rules previously established for the case in which only consumers suffer harm (strict liability dominates no liability and negligence) may be reversed if harm to third parties or the environment is sufficiently important.
Keywords: K13; 330; Liability; Cumulative harm; Environmental harm